2003
DOI: 10.1097/01.nmd.0000071588.73571.3d
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Distress and Coping Strategies Among Rescue Workers After an Earthquake

Abstract: Disaster workers are at high risk for developing psychiatric morbidity. This study examined the prevalence rates of psychiatric and posttraumatic distress and the relationship between psychiatric and posttraumatic morbidity and coping strategies among rescue workers following an earthquake in Taiwan on September 21, 1999. Eighty-four male firefighters who had been exposed to earthquake rescue work were assessed 5 months after the event. The Chinese Health Questionnaire (CHQ), the Impact of Event Scale (IES), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
6
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(75 citation statements)
references
References 30 publications
9
59
6
1
Order By: Relevance
“…Many papers exploring post-earthquake PTSD have been published in the last 5 years [7][8][9][10][11][12][13][14][15][16][17][18][19][20]; however, the reported prevalence of this dysfunction was assessed from 3 to 20 months after the seismic disturbance, and long-term follow-up results were lacking. One of these reports investigated the incidence of PTSD and MDE 20 months after the 1999 earthquake in Turkey, with © 2006 The Authors Journal compilation © 2006 The Royal Australian and New Zealand College of Psychiatrists estimated rates of 39% and 18%, respectively, demonstrated for non-treatment-seeking earthquake survivors [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many papers exploring post-earthquake PTSD have been published in the last 5 years [7][8][9][10][11][12][13][14][15][16][17][18][19][20]; however, the reported prevalence of this dysfunction was assessed from 3 to 20 months after the seismic disturbance, and long-term follow-up results were lacking. One of these reports investigated the incidence of PTSD and MDE 20 months after the 1999 earthquake in Turkey, with © 2006 The Authors Journal compilation © 2006 The Royal Australian and New Zealand College of Psychiatrists estimated rates of 39% and 18%, respectively, demonstrated for non-treatment-seeking earthquake survivors [19].…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress disorder can be triggered by profoundly traumatic events such as earthquake, and the adaptive dysfunction is strongly associated with the development of all other psychiatric disorders [3,[6][7][8][9]. The reported prevalence range for post-earthquake psychiatric disorders varies widely (1.5-74%) [3][4][5][9][10][11][12], with the female gender predominating [4,5,8,12].…”
mentioning
confidence: 99%
“…More culturally validated interview methods are needed in research that correlates ecological measures with individual stress regulation and coping among high-risk groups. Connor, Davidson, and Lee (2003) conducted a large-scale online survey of trauma survivors. They explored the contributions of spirituality, forgiveness, and anger to physical and mental health outcomes, using regression analysis.…”
Section: Assessment Approaches Consistent With a Cultural-ecological mentioning
confidence: 99%
“…Chang et al (2003) found that 21.4% of male firefighters who were involved in the Chi-Chi earthquake rescue work showed posttraumatic morbidity (CIES ≥ 26) and 16.7% reported generally psychiatry morbidity (CHQ ≥ 4). Predictors for PTSD symptoms were longer job experience, distancing, escape-avoidance, and lack of positive appraisal.…”
Section: Rescue Workersmentioning
confidence: 99%
“…39 Several studies have shown that rescue workers are at risk for post-traumatic stress disorders. [40][41][42][43][44] Other mental health complaints have also been found, including sleeping problems, 45 and anxiety or depression. 46 47 In contrast, however, several studies have shown that rescue workers may be regarded as a highly resilient group of professionals with regard to the potentially harmful effects of stress.…”
Section: Discussionmentioning
confidence: 99%